THE INFLUENCE OF CONFLICT AND OCCUPATIONAL HEALTH AND SAFETY ON WORK PRODUCTIVITY THROUGH MOTIVATION AT PT. KARYA MUDA NASIONAL IN MANDAILING NATAL - Indah Annisa; Prihatin Lumbanraja; Yeni Absah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to analyze the low productivity of employees over the past 3 years, improper work equipment, absence of medical checks before carrying out work, incomplete attributes for working in the field and absence of old age insurance for employees. The type of research used in this research is associative research. The population in this study were PT Karya Muda Nasional employees with 80 respondents as the sample. Data collection methods used are using questionnaires, interviews and documentation studies. The data analysis method uses Structural Equation Modeling in Partial Least Square. The results of this study found that conflict has a negative and insignificant effect on employee productivity,